(untitled) (Proceedings of the International Conference on Future of Women, 2025)
This study tries to find out the gender inequalities within the spaces of Colonial Clubs historically dominated by European men and the formation of Lady’s Clubs as a counter-movement. This study examines the patriarchal norms which systematically restricted the socio, political and economic freedom of women. And the intersectional aspects like race, gender and class. I have used records like Rules and Laws of Princes of Wales Ladies Club, Bhopal, Rules and Bylaws of Nilgiri Ladies Club, Ootacamund, Malabar European Club by law, Cochin saga an autobiography of Robert Bristow chief engineer of Cochin port, a biography of Sarojini Naidu and the records of Cochin Club, Munnar high range club, Archival documents and Malayalam literature for this study. Through an extensive survey of these documents, this research investigates how British and native men utilized exclusive clubs as a retreat space in Colonial India. This paper aims to shed light on the experiences of wives and other women impacted by this escapism. Club records and Malayalam literature frequently highlight a recurring issue: husbands spend evenings and weekends at clubs, engaging in social activities, while their wives and children feel abandoned and neglected. Many have questioned why husbands fail to include their wives in their social circles, even as a club member. This continued exclusion and the formation of many other women’s associations and social reform movements created a background for the emergence of Lady’s Clubs. The second half of the 19th century saw the rise of ladies’ clubs across India (e.g., the Princes of Wales Club and the Nilgiri Ladies Club). The analysis focuses on how these clubs empowered women through activities, decision-making opportunities, and fostering social connections. The private and public worlds merger continued in clubs of the postcolonial era. Women have gained greater access to these spaces, though challenges to gender equality may persist in some clubs.